Herbert Simon’s spell on judgment and decision making - Konstantinos V. Katsikopoulos; Cherng-Horng (Dan) Lan (Judgment and Decision Making, 2011)
How many judgment and decision making (JDM) researchers have not claimed to be building on Herbert Simon's work? We identify two of Simon's goals for JDM research: He sought to understand people's decision processes---the descriptive goal---and studied whether the same processes lead to good decisions---the prescriptive goal. To investigate how recent JDM research relates to these goals, we analyzed the articles published in the Journal of Behavioral Decision Making and in Judgment and Decision Making from 2006 to 2010. Out of 377 articles, 91 cite Simon or we judged them as directly relating to his goals. We asked whether these articles are integrative, in the following sense: For a descriptive article we asked if it contributes to building a theory that reconciles different conceptualizations of cognition such as neural networks and heuristics. For a prescriptive article we asked if it contributes to building a method that combines ideas of other methods such as heuristics and optimization models. Based on our subjective judgments we found that the proportion of integrative articles was 67% of the prescriptive and 52% of the descriptive articles. We offer suggestions for achieving more integration of JDM theories. The article concludes with the thesis that although JDM researchers work under Simon's spell, no one really knows what that spell is.